2015
DOI: 10.1262/jrd.2014-130
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione supplementation to semen extender improves the quality of frozen-thawed canine spermatozoa for transcervical insemination

Abstract: The present study was conducted to evaluate whether supplementation of semen extender with glutathione (GSH) can maintain the quality of frozen-thawed canine spermatozoa. Eighteen ejaculates were obtained from 5 dogs and placed in extender (20% egg yolk, Tris, citric acid, lactose, raffinose, antibiotics and 6.5% glycerol) containing 0 (control), 2.5, 5, 7.5 or 10 mM GSH. The samples were cooled to 4 C and then frozen in liquid nitrogen vapor. Motility parameters of the sperm were evaluated at 0, 1, 2, 3, 4, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 46 publications
1
26
1
Order By: Relevance
“…only in chilled samples) analyzed by the cytochemical technique of 3.3' diaminobenzidine. These results show that control and GSH in 5mM concentration promotes a better mitochondrial functionality which can reflect in an increased in motility rates and may improve pregnancy, such as previously described (Ogata et al, 2015). Thus, despite our motility results (by CASA) show no changes, this parameter should be better investigated in futures studies.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…only in chilled samples) analyzed by the cytochemical technique of 3.3' diaminobenzidine. These results show that control and GSH in 5mM concentration promotes a better mitochondrial functionality which can reflect in an increased in motility rates and may improve pregnancy, such as previously described (Ogata et al, 2015). Thus, despite our motility results (by CASA) show no changes, this parameter should be better investigated in futures studies.…”
Section: Discussionsupporting
confidence: 57%
“…GPx; GSH and PHGPx) combined with SOD had an important effect in ROS combat, because this enzymes catalyse the chain reaction in which superoxide anion (O2 -), the first produced ROS, is converted into water (H 2 O 2 ) (Cadenas and Davies, 2000). Moreover, glutathione develops an important function in the preservation of membrane integrity against lipid peroxidation, sperm motility and avoid premature acrosome reaction (Alvarez and Storey, 1989;Rejraji et al, 2002;Gadea et al, 2013). Therefore, antioxidant supplementation (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Innovative methods for the cryopreservation of canine semen facilitate the transfer of desirable genetic material from the most valuable stud dogs, contribute to the preservation of endangered canine breeds, and enhance the utilisation of specific genetic traits in male dogs ( 32 ). Recent research has contributed valuable information about the role of genes encoding behavioural and personality traits in dogs, including assistance dogs ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several substances were used to increase the quality of cryopreserved sperm cells in canine species to mitigate the adverse effect of cryopreservation: ascorbic acid and glutathione, alone or in association, were added to the freezing medium and exerted a positive effect on post thawing sperm longevity and viability [6]. In addition, a more recent study showed positive effects of glutathione on sperm quality and fertility when added to the freezing medium [7]. Vitamin C, N-acetyl-Lcystein, taurine, catalase, vitamin E and vitamin B12 were added to the freezing extender separately [5]; that study demonstrated that antioxidant exerted positive effects on dog semen but the most effective one was catalase.…”
Section: Introductionmentioning
confidence: 99%